Cancer immunology II: molecular and cellular bases of carcinogenesis - de León, Joel (2019)
Technological advances applied to preclinical and clinical scientific research have significantly enabled the broadening of knowledge regarding neoplastic cells biology in the last two decades. The characterization of genetic and epigenetic alterations which are involved in carcinogenesis; the molecular subclassification of tumors; the understanding of normal and neoplastic cells interactions in the tumor microenvironment; and the description of molecular bases that explain the influence of factors such as exercise, diet and microbiota composition on cancer progression have contributed to support the importance of precision medicine in cancer. The present research reviews the so-called "hallmarks of cancer" and their "enabling characteristics", i.e. those properties inherent to cancer cells that allow to evade intrinsic and extrinsic mechanisms of carcinogenesis control. This paper is a follow-up review of studies on cancer immunology that started with the presentation of the molecular and cellular bases of the anti-tumoral immune response, and will eventually focus on the manipulation of the relationship between the immune system and malignancies as a cancer treatment strategy.